Racially and ethnically diverse women leading education a world view - Watson, Terri N.; Normore, Anthony H. (Bingley, U.K. : Emerald, 2016)
This book's primary focus is on racially and ethnically diverse women in educational leadership. Each chapter is written from a unique conceptual or empirical lens as shared by international female leaders. Of particular interest to readers is the ingenious pairing of contributors for optimum scholarship, whereby the majority of chapters are co-authored by at least one male in a leadership role who shares in the crusade for social, cultural, political, and economic gender and racial equality for effective leadership that works. The general content is framed by but not limited to theoretical frameworks such as Black / Feminist Thought, Critical Race Theory, and Leadership for Social Justice. The chapters range from a critical examination of global society and cross-cultural collaboration, to the intersection of race, law, and power. Each chapter illuminates the lives and experiences of racially and ethnically diverse women in leadership positions in a diverse range of educational settings and contexts.
Paradigm shift or paradigm stasis? an analysis of research on U.S. women in educational leadership from 1980-2004 / Terri N. Watson, Dianne W. Hodgins, Jeffrey S. Brooks -- Leadership structures of major international organizations: an exploration of gender and regional disparities / Shazia K. Jan, Moosung Lee, Yuk Ling Keri Chui -- Negotiating race and gender in marginalized work settings / Gaetane Jean-Marie, Anthony H. Normore, Katherine Mansfield -- Emiratiyat embracing a shifting world: ways of knowing leadership in the United Arab Emirates / Marilyn R. Davis, Majed Abu Jaber, Rabaa AlSumaiti, Boyce Courtney Williams -- Women, leadership, and education as change / Ellyn Lyle, Dustin MacLeod -- African American women leaders in higher education / Dianne Wright, Cristobal Salinas Jr. -- Gender, ethnicity and social justice leadership: female Jewish and Arab school principals in Israel / Khalid Arar, Asmahan Masry-Herzalah -- Te Ara Hou - the Maori Achievement Collaboratives (MACS): revolutionizing Indigenous student learning through women's educational leadership in Aotearoa New Zealand / Lorri J. Santamari<U+0301>a, Andres Santamaria, Melinda Webber, Sharona Jayavant -- Let me act the part of a man: duality of genders towards critical leadership / Mere Berryman, John Tait -- Done well or not done at all: increasing minority women's representation in leadership / Brent Johnson, Shewanee Howard-Baptiste -- Navigating the path of critical leadership: tensions and possibilities of the leadership journey / Ann Lopez, Gale Solomon-Henry -- Filipino women as educational leaders: widening windows of opportunities in ASEAN 2015 / Maribel Valdez, Alice G. Comahig -- Ethical decision making among women education leaders: a case of Nepal / Prakash C. Bhattarai, Jamuna Maharjan -- Authenticity and the female African American school leader / Rabin Nickens, Carland Washington -- Just give the money to the women: overly simplified advice that works in international education, health and development initiatives / C. Darius Stonebanks, Fintan Sheerin, Melanie Bennett-Stonebanks, Jenala Nyirenda-Paradise -- Teacher candidates' perceptions on female and male leadership candidates' leadership styles / Soribel Genao, Nathalis Wamba -- Epilogue: linking our stories to a common enemy? / Ira E. Bogotch.
Includes bibliographical references.
Print version record
Keywords: Education -- Administration -- General; Education; Women school administrators; Minority women educators; Educational leadership